Modeling magnetopause location for 4D drift-resolved radiation belt codes: Salammbô model implementation - R. Kiraz; N. Dahmen; V. Maget; B. Lavraud (Annales Geophysicae)
We present a new semi-analytical magnetopause location model specifically designed for 4D drift-resolved radiation belt modeling codes. We specifically designed this magnetopause location model for the 4D version of Salammbô, but it can be adaptable to similar codes. The model combines parameterization by the Kp index with a representation of the magnetopause in L∗ geomagnetic coordinates and magnetic local time (MLT). It is based on a 20-year dataset relying on computed magnetopause stand-off distances using a solar wind database and a relevant magnetopause model, then converted into L∗ geomagnetic coordinates for all dayside MLT. Through the statistical analysis of this dataset, the model was formulated and validated against a magnetopause crossing catalog. Its performance was benchmarked against the magnetopause location model previously developed for the 3D version of the Salammbô code. The results demonstrate an improvement in predicting the magnetopause position in L∗ across dayside MLT sectors, with enhanced accuracy in the dawn sector. These results highlight the model's ability to model the magnetopause location in L∗ across dayside MLT sectors. This advancement may be specifically useful for simulating magnetopause shadowing in ring current and radiation belt modeling codes.